Effects of thermal and electrical stress on defect generation in InAs metal-oxide-semiconductor capacitor - Baik, Min; Kang, Hang-Kyu; Kang, Yu-Seon; Jeong, Kwang-Sik; Lee, Changmin; Kim, Hyoungsub; Song, Jin-Dong; Cho, Mann-Ho (ELSEVIER SCIENCE BV, 2019)
Defects in HfO2 dielectric film caused by indium and arsenide diffusion from InAs were investigated. To investigate the dissociation of InAs during post-deposition annealing (PDA) at 600 degrees C, we analyzed the ratio of the elements on the surface of the oxide layer and the chemical states by using time-of-flight secondary-ion mass spectroscopy and X-ray photoelectron spectroscopy, respectively. In-As bonding was dissociated and In and As atoms were diffused through the HfO2 layer from InAs. Fortunately, the diffusion and trap density could be controlled by using a 1-nm-thick Al2O3 passivation layer. In addition, we used the nitridation process to control the trap density. We evaluated the thermal and electrical stability of three samples-HfO2/InAs, HfO2/Al2O3/InAs, and nitrided HfO2/Al2O3/InAs-by analyzing the change in trap density before and after PDA at 600 degrees C and the stress-induced leakage current. In conclusion, the passivation layer effectively improved the thermal and electrical stability, whereas the nitridation process using NH3 gas did not. Moreover, although nitridation could reduce the interfacial defect states, due to structure distortion, it induced the degradation of the device.
Keywords: ATOMIC-LAYER-DEPOSITION; HFO2; EVOLUTION; FILMS; INP